Unani methods of cure in the Indian subcontinent: An analytical study - Islam, Arshad (2017)
The history of medicine is bound up with the history of human civilization and life, representing the complex interactions of human communities, geography and the environment over time. South Asia has always been a strong and vibrant melting pot and a crossroads of interactions between different peoples. A clear example of this is Unani (‘Greek’) medicine, based on ancient Hellenic thought (via its interactions with Babylonian, Egyptian, Indian and Persian knowledge), which formed the basis of ‘modern’ Western medicine as well as Ayurvedic treatment. Tibb-iUnani is Arabic for ‘Greek medicine’, which became Unani as practiced in the Indian Subcontinent, where it was developed and refined through systematic experimentation by renowned scholars. Muslim physicians tested Indian traditional medicines using clinical trials, as a result of which they incorporated a number of indigenous medicines in their own system, advancing and enriching its treasures. This formed the basis of medical science in India until the British occupation, resulting in a number of classical medical works during this period that evidence organized and advanced medical care in India. The basic Unani framework is timeless, based on human action and intrinsic causes. This paper highlights the aspects of Indian contributions to classical Unani medicine that are subtle and perhaps more important to the development of the entire body of scientific knowledge. Through an analysis of socio-cultural and historical context, the paper concludes that the contribution of Unani medicine in India lies in: (a) preserving the ancient Greek tradition of medicine, and (b) safeguarding and advancing utilitarian medical science and treatment into the early modern period. While this archetypal ancestor of modern medicine has been forgotten in the rest of the world, it remains a vibrant living tradition in South Asia. This paper emphasizes the Unani system of cure in India as an alternative traditional medicine using Arabic, Sanskrit, Persian, Urdu and English sources.